2020
DOI: 10.3390/diagnostics10020114
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR Test for Rapidly and Sensitively Detecting Circulating EGFR Mutations

Abstract: The detection of EGFR mutations in circulating cell-free DNA can enable personalized therapy for cancer. The current techniques for detecting circulating EGFR mutations are expensive and time-consuming with moderate sensitivity. Emerging CRISPR is revolutionizing medical diagnostics and showing a great promise for nucleic acid detection. This study aims to develop CRISPR-Cas12a as a simple test to sensitively detect circulating EGFR mutations in plasma. Serially diluted samples of DNA containing heterozygous E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…27,28 One of the main advantages of the IMPACT chip compared to traditional CRISPR assays is its ability to limit the background caused by dye-quencher probes, which is typically seen in CRISPR detection in the liquid state and needs to be designed around to lower the detection limit. 29,30 Our device utilizing solid-phase CRISPR does not need to tether a quencher on the probe. The cleaved CRISPR products are sent to a separate reservoir for detection thus completely avoiding the fluorescence background caused by the tradition "onepot" detection.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 One of the main advantages of the IMPACT chip compared to traditional CRISPR assays is its ability to limit the background caused by dye-quencher probes, which is typically seen in CRISPR detection in the liquid state and needs to be designed around to lower the detection limit. 29,30 Our device utilizing solid-phase CRISPR does not need to tether a quencher on the probe. The cleaved CRISPR products are sent to a separate reservoir for detection thus completely avoiding the fluorescence background caused by the tradition "onepot" detection.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids of KRAS mutation G12C and G12S (#83167 and #83144) in Escherichia coli DH5α were obtained from Addgene (Addgene, Watertown, MA, USA) and grown in LB medium with 50 µg/mL Streptomycin in a shaking incubator. Plasmid DNA was isolated by using our previously developed protocols [ 9 , 10 ]. DNA concentration was measured by using the Quantifiler Human DNA Quantification kit (Applied Biosystems, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction. We extracted DNA using the DNeasy kit (Qiagen, Valencia, CA, USA) as described in our previous publications [ 9 , 10 , 11 , 12 , 13 , 14 ]. We eluted DNA with 50 μL of elution buffer (10 mmol/L Tris-Cl, pH 8.5) (Sigma-Aldrich Corporation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study has demonstrated that CRISPR-Cas12a can detect nucleic acids of exogenous viruses, such as human papillomavirus, in the raw plasma of cervical cancer patients without requiring RNA extraction [ 12 ]. Our research has also demonstrated that the CRISPR-based test can rapidly and sensitively detect endogenous DNA mutations of EGFR and KRAS in plasma and tissue specimens of lung cancer patients [ 13 , 14 ]. Recently, we developed CRISPR-Cas12a as a rapid test for sensitive detection of SARS-CoV-2 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%